Hydrogen storage in carbon aerogels - Tian, Hu-Yong; Buckley, Craig; Paskevicius, Mark; Sheppard, Drew (Taylor & Francis Group, 2012)
Hydrogen storage issues have been universally investigated in order to satisfy the goals for a hydrogen economy. Carbon aerogels are regarded as one of the most promising candidates for hydrogen storage at cryogenic temperature (77 K) because they have ultra fine cell/pore sizes, continuous porosity, and high surface areas. Discussed in this chapter is the synthesis and characterization of various carbon aerogels. Carbon aerogels were prepared from the sol-gel polymerization of resorcinol with furfural followed by carbonization and activation. The effect of pH values on microstructures of carbon aerogels were studied using acetic acid and potassium hydrate catalysts. Furthermore, an efficient and simple synthesis method was employed to prepare cobalt doped carbon aerogels. The chemical reaction mechanism and optimum synthesis conditions were further investigated by Fourier Transform Infrared Spectroscopy and thermo analyses with a focus on the sol-gel process. The carbon aerogels were investigated with respect to their microstructures, using small angle x-ray scattering and nitrogen adsorption measurements at 77 K. Hydrogen storage properties were investigated at room temperature and liquid nitrogen temperature at pressures up to 6.5 MPa.1.1Hydrogen storage issues have been universally investigated in order to satisfy the goals for a hydrogen economy. Carbon aerogels are regarded as one of the most promising candidates for hydrogen storage at cryogenic temperature (77 K) because they have ultra fine cell/pore sizes, continuous porosity, and high surface areas. Discussed in this chapter is the synthesis and characterization of various carbon aerogels. Carbon aerogels were prepared from the sol-gel polymerization of resorcinol with furfural followed by carbonization and activation. The effect of pH values on microstructures of carbon aerogels were studied using acetic acid and potassium hydrate catalysts. Furthermore, an efficient and simple synthesis method was employed to prepare cobalt doped carbon aerogels. The chemical reaction mechanism and optimum synthesis conditions were further investigated by Fourier Transform Infrared Spectroscopy and thermo analyses with a focus on the sol-gel process. The carbon aerogels were investigated with respect to their microstructures, using small angle x-ray scattering and nitrogen adsorption measurements at 77 K. Hydrogen storage properties were investigated at room temperature and liquid nitrogen temperature at pressures up to 6.5 MPa.